Desain Datapath Arsitektur Komputer MIC-1 8 bit Menggunakan IC74XX - Seprianto Ray Roganda Sianipar; Mochammad Hannats Hanafi Ichsan; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The architecture of the MIC-1 8 bits is one of the simplest computer architecture in which there are registers such as the program counter, a memory buffer register, register A, register B, an external input and integrated logic unit. The register collection was used as a datapath for the execution of instructions. Intergrated circuit 74XX (IC74XX) is an intergrated circuit (IC) series used to implementation simple logical series. IC74XX, in one set of IC74XX, there are several varieties of gates that can perform a variety of functions involving AND, OR, NOT, adder, and multiplexer. On a series of datapath computer architecture MIC-1 8 bits uses switches and IC74051. The switch function is as a data input entered by the user by hand and IC74051 to process datapath data that is used as a b bus input. Arihmetic logic unit (ALU) using IC74LS32, IC74LS04, IC74LS08, IC74LS08, and IC74LS251N in the arithmetic and logic process. Datapath and arithmetic logic unit (ALU) use 5-volt power as resources and LED as output. With functional testing results it obtained according to manual calculations in multiplexer datapath operation and was reduced to non-functional testing part.